1974
DOI: 10.1161/01.res.35.3.464
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Ventricular Excitability Characteristics to Ventricular Arrhythmias in Dogs

Abstract: The relationship of the form of ventricular anodal strength-interval curves to the types of arrhythmias induced by trains of low-intensity stimuli was studied in 16 dogs. Strength-interval curves were determined after basic atrial driven beats and after induced premature ventricular depolarizations. The test stimuli for these determinations were 2-msec anodal square waves delivered in 1-msec decrements during the first half of the cardiac cycle and in 10-msec decrements during the last half of the cycle. At ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In the present study, both epicardial and endocardial strength-interval curves have been found to exhibit a smooth hyperbolic shape with no dips on the steep descending portion of the curve (Fig. 2), suggesting that no supernormal excitability phase, an attribute of anodal break-excitation (20,33,45), was yielded by bipolar stimulations.…”
Section: Main Findingssupporting
confidence: 58%
See 2 more Smart Citations
“…In the present study, both epicardial and endocardial strength-interval curves have been found to exhibit a smooth hyperbolic shape with no dips on the steep descending portion of the curve (Fig. 2), suggesting that no supernormal excitability phase, an attribute of anodal break-excitation (20,33,45), was yielded by bipolar stimulations.…”
Section: Main Findingssupporting
confidence: 58%
“…Previous studies have demonstrated close correlation between diastolic excitability threshold and VF threshold values (15,29,33,36,62), suggesting that increased tissue excitability may facilitate VF induction. The LV was found to be most susceptible to electrically induced VF at those intervals of the cardiac cycle at which the ventricular capture threshold is the lowest (15,33,36).…”
Section: Main Findingsmentioning
confidence: 83%
See 1 more Smart Citation
“…Choosing too low a suprathreshold current results in the choice of an interval that would change significantly with only slight changes in current. Because there is no final conclusion about which electrical parameters best describe the refractoriness properties of the cells during in vivo conduction, twice diastolic threshold was used in the present study, and has been used routinely in other electrophysiological studies (Denes et al, 1974;Harumi et al, 1974;Levites et al, 1975). Allessie et al (1978) determined in isolated atrial strips that a refractoriness gradient of 11-16 msec was sufficient to cause conduction block.…”
Section: Measurements Of the Recovery Of Excitabilitymentioning
confidence: 99%
“…'"'In the past, cardiac excitability has been assessed primarily in the whole animal, and the index investigated has been the "threshold" current sufficient to elicit a response in studies on either strength-duration requirements or multiple response thresholds. 8 ' 9 Conflicting results appear in the literature, with some studies showing procaine amide (PA) to decrease excitability in a variety of species, 10 " 12 whereas one failed to show any significant effect. 13 Although in these studies there are many differences in experimental technique, part of the variability in the results may be attributed to the fact that the "current threshold" is determined by a complex set of passive and active membrane properties.…”
Section: The Effect Of Procaine Amide On Components Of Excitability Imentioning
confidence: 99%